Efeitos do aumento da transmissão dopaminérgica durante o período de adolescência sobre o comportamento sexual de ratos adultos - Pires, Jhon Helbert Soterio [UNIFESP] (2017)
During adolescence, the nervous system is in continuous change and dopaminergic receptors D1 e D2 are highly express. It is known that stressful and rewarding events are able to activate dopaminergic pathways and this may have long term consequences. This project evaluated if the increase of the mesolimbic dopaminergic transmission during the adolescence period cause damage in the sexual behavior of adult rats. Wistar male rats were distributed in 6 groups according to natural or pharmacological stimulation. Control (CTRL, without manipulation), sleep restriction (SR, 18 hours per 21 days) and sexual behavior (SB) constituted the natural stimulation groups. Control saline (CTRL salt, 1mL/kg), cocaine (COC, 15 mg/kg) e apomorphine (APO, 120 μg/kg) constituted the pharmacological stimulation groups. Protocols occurred in the adolescence period (35° to 56° days) at each 3 days intervals, with the exception of SR, which was continuous. When rats completed the adult stage (80 days), they were submitted to 3 tests of sexual behavior weekly. Also, it was evaluated the anxious behavior in open field test and the dopaminergic activation in stereotypic test. In the following day, animals were euthanized by decapitation and blood was collected for hormonal quantification. Results showed that between the natural stimulation groups, in the third sexual behavior test, latency of ejaculation increased while number of ejaculations decreased in the SB group compared to the SR; whereas in the first and second tests no significant difference was observed. Within the pharmacological stimulation groups, the APO group demonstrated reduction of the inter-copulatory and inter-intromission intervals compared with the CTRL saline group in the first test of sexual behavior. In the second sexual behavior test, the APO group showed lower copulatory index in comparison with CTRL saline group. Open field and stereotypic tests, as well as hormonal concentration of total testosterone, progesterone and corticosterone did not showed significant differences within the pharmacological and natural stimulation groups. Results indicated that apomorphine use during adolescence caused small impairment of sexual behavior in adulthood probably because of the low dose administrated in a long period of time. Taken together, this study shows promise for others studies aiming to investigate the mesolimbic system associated with the reward system during different stages of life, in other social and biological environments.